Detoxification mechanisms in shrimp: Comparative approach between hydrothermal vent fields and estuarine environments - Gonzalez-Rey, Maria (2020)
Hydrothermal vents are extreme deep-sea habitats that, due to their singular features, still intrigue scientific communities. Swift growth rates and profuse biomass of biological communities can be observed, despite of their inherently unstable physical-chemical and toxic conditions, indicating that organisms inhabiting this environment must be well adapted to these inhospitable conditions. The caridean shrimp, Chorocaris chacei, Mirocaris fortunata and Rimicaris exoculata, together with bathymodiolid mussels, dominate the vent fauna along the Mid-Atlantic Ridge (MAR). Crustacean species are widely used as biological indicators of environmental alterations, since they play a key ecological role as planktivorous grazers, epibenthic scavengers or as prey species. The biological consequences of the hydrothermal metal-rich environment in shrimp species are still largely unknown. Therefore, the aim of this study was the determination of the metal levels (Ag, Cd, Cu, Fe, Mn and Zn), metallothioneins (MT) and lipid peroxidation (LPO) in shrimp species collected in Rainbow, Lucky Strike and Menez-Gwen vent sites, in order to evaluate their different adaptation strategies toward metals when compared with two common coastal shrimp species (Palaemon elegans and Palaemonetes varians) from a fairly unpolluted estuarine system in south Portugal (Ria Formosa). Results show significant differences in metal concentrations, MT levels and lipid peroxidation between vent and coastal shrimp and also between shrimp species from the same site. This indicates that biochemical responses in both vent and coastal shrimp are affected not only by the environmental characteristics but also by inter-specific differences. Nevertheless, these responses apparently grant a successful adaptation for the survival in a metal-extreme environment.